2019
DOI: 10.25270/wmp.2019.2.1419
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Study of Hospital- and Community-acquired Pressure Ulcers/Injuries

Abstract: Hospital-acquired pressure ulcers/injuries (HAPU/I) have been a major focus of research, but information about community-acquired pressure ulcer/injuries (CAPU/I) is limited. PURPOSE: The aim of this study was to compare HAPU/I and CAPU/I in a 620-bed academic medical center in the western United States. METHODS: This descriptive study involved prospective/ retrospective data collected from the National Data for Nursing Quality Indicators, including pressure ulcer stage (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…As a result, the facility was able to where to focus education for pressure injury prevention. 13 The multidisciplinary team's ability to curate an MVP database has significant implications as well. High utilizers of ED care are at increased risk for adverse outcomes, such as medical errors and frequent rehospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the facility was able to where to focus education for pressure injury prevention. 13 The multidisciplinary team's ability to curate an MVP database has significant implications as well. High utilizers of ED care are at increased risk for adverse outcomes, such as medical errors and frequent rehospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Open wounds, particularly deep chronic wounds such as pressure ulcers/injuries (PUs/PIs) classified as category‐3/4 and diabetic foot ulcers (DFUs) continue to be a major and snowballing threat to global public health and the economy. For example, the prevalence of PUs/PIs in the general population is 11 of 100 000 people, but rises to approximately 5% and 10% for community and adult/paediatric acute healthcare settings, respectively, rendering this condition as the third most costly disease to treat after cancers and cardiovascular diseases 1‐6 . Likewise, the global prevalence of DFUs is approximately 6% (630 per 100 000 diabetic individuals) and the total cost for management of diabetic foot disease ranges from 9 to 13 billion dollars only in the United States, in addition to the cost of managing the diabetes alone 7‐9 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the prevalence of PUs/PIs in the general population is 11 of 100 000 people, but rises to approximately 5% and 10% for community and adult/paediatric acute healthcare settings, respectively, rendering this condition as the third most costly disease to treat after cancers and cardiovascular diseases. 1 , 2 , 3 , 4 , 5 , 6 Likewise, the global prevalence of DFUs is approximately 6% (630 per 100 000 diabetic individuals) and the total cost for management of diabetic foot disease ranges from 9 to 13 billion dollars only in the United States, in addition to the cost of managing the diabetes alone. 7 , 8 , 9 It is well established that negative pressure wound therapy (NPWT) is an effective wound care approach for treating and managing these tissue damage conditions.…”
Section: Introductionmentioning
confidence: 99%
“…5 It was reported that the point prevalence of present-on-admission pressure injuries (POA-PIs) was 6.9%, which was much higher than hospital-acquired pressure injuries(HAPIs) (0.9%). 6 This means that, compared with HAPIs, POA-PIs are more common among hospitalized patients but scant attention has been paid to them 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the existing studies focusing on POA-PI are limited to the prevalence, 4,6,7,8 and only a few studies have analyzed the characteristics of POA-PI patients: After analyzed the age, gender and length of stay(LOS) of POA-PI patients, Peter et al…”
Section: Introductionmentioning
confidence: 99%